Enhancements to Society's Products and Services: Report of Progress Made in 2008. - Kasturi, Rangachar (Computer (00189162), 2008)
In this article the author discusses the Computer Society's progress reports in regard to revitalization efforts in 2008. The author focuses on the relaunch of computer.org, the launch of the software developer certification program, and the development of several webinars and podcasts, as well as technology summits.